1980
DOI: 10.3168/jds.s0022-0302(80)83132-8
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Urea Metabolism in Ruminants with Reference to the Goat

Abstract: In goats and other ruminants, urea functions as a source of nitrogen for protein biosynthesis in the digestive tract. Ammonia can be absorbed in the digestive system when formed in excessive quantitites and enhance formation of urea, or it can be derived from urea of blood plasma when its formation from feed sources is small. Entry rates of urea into plasma may vary from 4 to 80 mumol/min per kg.75 body weight depending on dietary conditions. Urea formation is related to nitrogen intake of which approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
117
2
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 56 publications
14
117
2
21
Order By: Relevance
“…However, the intercept of the linear regression observed by these authors was significant, whereas in this current meta-analytical approach it was not significant. According to Harmeyer and Martens (1980), N intake is the major factor influencing UER; they observed a correlation of 0.88 between these variables, which was similar to the current study (r = 0.91). These authors found that the feeding schedule (twice daily or feeding hourly), site of N supplied to the animal (oral or abomasal), and type of N fed (non-protein N v. true protein) did not affect significantly the amount of urea synthesized in the liver.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, the intercept of the linear regression observed by these authors was significant, whereas in this current meta-analytical approach it was not significant. According to Harmeyer and Martens (1980), N intake is the major factor influencing UER; they observed a correlation of 0.88 between these variables, which was similar to the current study (r = 0.91). These authors found that the feeding schedule (twice daily or feeding hourly), site of N supplied to the animal (oral or abomasal), and type of N fed (non-protein N v. true protein) did not affect significantly the amount of urea synthesized in the liver.…”
Section: Discussionsupporting
confidence: 89%
“…The UUE is one of the fates of the urea synthesized in the liver and released into blood, and factors such as N intake relative to nutritional requirements affect it (Huntington and Archibeque, 1999). According to Harmeyer and Martens (1980), the kidney has specific mechanisms that modify urinary urea N excretion (or reabsorption). The amount of urea excreted by the kidneys may be influenced by three main factors: changes of PUN and corresponding changes in filtered urea loads, variations of the glomerular filtration rates, and modifications of tubular reabsorption of urea (Harmeyer and Martens, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations